Handbuch Bibliothek 2.0 Handbook Library 2.0 - Bergmann, Julia (Bibliotheks- und Informationspraxis, 2010)
With the term "Library 2.0" the editors mean an institution which applies the principles of the Web 2.0 such as openness, re-use, collaboration and interaction in the entire organization. Libraries are extending their service offerings and work processes to include the potential of Web 2.0 technologies. This changes the job description and self-image of librarians. The collective volume offers a complete overview of the topic Library 2.0 and the current state of developments from a technological, sociological, information theoretical and practice-oriented perspective.